Scenes from Shakespeare fifteen cuttings for the classroom - Shakespeare, William 1564-1616 (Meriwether Pub., 1993)
A collection of fifteen short scenes from five Shakespeare plays: "Romeo and Juliet," "The Merchant of Venice, " "Julius Caesar, " "Othello, " and "Hamlet." Each scene is preceded by a plot synopsis and descriptions of the characters.